The cortical protein Lte1 promotes mitotic exit by inhibiting the spindle position checkpoint kinase Kin4 - Bertazzi Lazzarini, Daniela Trinca; Kurtulmus, Bahtiyar; Pereira, Gislene (The journal of cell biology, 2011)
The spindle position checkpoint (SPOC) is an essential surveillance mechanism that allows mitotic exit only when the spindle is correctly oriented along the cell axis. Key SPOC components are the kinase Kin4 and the Bub2-Bfa1 GAP complex that inhibit the mitotic exit-promoting GTPase Tem1. During an unperturbed cell cycle, Kin4 associates with the mother spindle pole body (mSPB), whereas Bub2-Bfa1 is at the daughter SPB (dSPB). When the spindle is mispositioned, Bub2-Bfa1 and Kin4 bind to both SPBs, which enables Kin4 to phosphorylate Bfa1 and thereby block mitotic exit. Here, we show that the daughter cell protein Lte1 physically interacts with Kin4 and inhibits Kin4 kinase activity. Specifically, Lte1 binds to catalytically active Kin4 and promotes Kin4 hyperphosphorylation, which restricts Kin4 binding to the mSPB. This Lte1-mediated exclusion of Kin4 from the dSPB is essential for proper mitotic exit of cells with a correctly aligned spindle. Therefore, Lte1 promotes mitotic exit by inhibiting Kin4 activity at the dSPB.